Editorial - Dossiê Cibereducação: fundamentos, interfaces e pedagogias emergentes - Santos, Edméa Oliveira dos; Oliveira, Fabiane Lopes de; Amante, Lúcia (Revista UFG, 2021)
Editorial - Dossiê Cibereducação: fundamentos, interfaces e pedagogias emergentes